Pengaruh Pemanfaatan E-Learning, Kemandirian Belajar, Sarana Pembelajaran Online, Dan Perhatian Orang Tua Terhadap Motivasi Belajar Ekonomi Peserta Didik Kelas X IPS SMA Negeri 1 Padang Cermin Tahun Pelajaran 2020/ 2021 - Kristiani Natalia Dalima; I Komang Winatha; Tedi Rusman (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
This reaserch was discusses the probleming of the low motivation to study economic for grade X of Social Science students at State 1 Padang Cermin Senior High School. Thus, the purpose of this research is to determine the level of economic learning motivation students at grade X of Social Science State 1 Padang Cermin Senior High School on Academic Year 2020/2021 during online learning at pandemic covid-19. The method used in this research was descriptive verificative with expost facto and survey approaches, with data collection techniques through observation, online interview, and questionnaire.. This reaserch was tested partially and simultaneously to 55 students. Based on the result of partially test, it was conclude that the effect of e-learning utilization (X1) on the economic learning motivation (Y) was 0.140 or 14%, learning independence (X2) on the economic learning motivation (Y) was 0.097 or 9.7%, online learning facilities (X3) on the economic learning motivation (Y) was 0.134 or 13.4%, and parental attention (X4) on the economic learning motivation (Y) was 0.147 or 14.7%. Based on the result of simultaneously test, it was conclude that there was an effect of e-learning utilization, learning independence, online learning facilities, and parental attention on the economic learning motivation of students Grade X of Social Science State 1 Padang Cermin Senior High School at Academic Year 2020/2021 which was 0.397 or 39.7% with the acquisition of Fcount Ftable or 8.243 2.56 and significant value (α) or 0.000 0.05